2005
DOI: 10.1038/sj.ijo.0802965
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diet-induced obesity by dietary isomerized hop extract containing isohumulones, in rodents

Abstract: OBJECTIVE: Isomerized hop extract (IHE), which consists mainly of isohumulones and is required in the beer brewing process, was investigated for its effects on diet-induced obesity in two strains of mice. DESIGN: C57BL/6N and KK-A y mice were fed a standard or high-fat diet containing IHE and their body and tissue weights were measured at various time points. Oral glucose tolerance tests (OGTT) and insulin tolerance tests (ITT) were carried out in high-fat diet-fed C57BL/6N mice. The effects of IHE on intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 23 publications
1
47
0
3
Order By: Relevance
“…Activators of PPAR, such as fibrates and isohumulones, lower body weight gain, retroperitoneal adipose tissue weight, plasma TG level, and hepatic TG content. 4,[14][15][16] We investigated to determine whether activation of PPAR is involved in the anti-obesity effects of Yamabushitake mushroom Mean values were significantly different from those of the control group: Ã p < 0:05; ÃÃ p < 0:01. Ppara, peroxisome proliferator-activated receptor (PPAR); Apoa1, apo A-I; Lpl, lipoprotein lipase; Slc27a1, fatty acid transport protein 1; Slc27a4, fatty acid transport protein 4; Acsl1, acyl-CoA synthetase long-chain family member 1; Acox1, palmitoyl acyl-CoA oxidase 1; Acadm, acyl-CoA dehydrogenase, medium chain; Acadl, acyl-CoA dehydrogenase, long-chain; Srebf1, sterol regulatory element binding factor 1; Fasn, fatty acid synthase; Acaca, acetyl-CoA carboxylase extracts in mice fed a high-fat diet.…”
Section: Discussionmentioning
confidence: 91%
“…Activators of PPAR, such as fibrates and isohumulones, lower body weight gain, retroperitoneal adipose tissue weight, plasma TG level, and hepatic TG content. 4,[14][15][16] We investigated to determine whether activation of PPAR is involved in the anti-obesity effects of Yamabushitake mushroom Mean values were significantly different from those of the control group: Ã p < 0:05; ÃÃ p < 0:01. Ppara, peroxisome proliferator-activated receptor (PPAR); Apoa1, apo A-I; Lpl, lipoprotein lipase; Slc27a1, fatty acid transport protein 1; Slc27a4, fatty acid transport protein 4; Acsl1, acyl-CoA synthetase long-chain family member 1; Acox1, palmitoyl acyl-CoA oxidase 1; Acadm, acyl-CoA dehydrogenase, medium chain; Acadl, acyl-CoA dehydrogenase, long-chain; Srebf1, sterol regulatory element binding factor 1; Fasn, fatty acid synthase; Acaca, acetyl-CoA carboxylase extracts in mice fed a high-fat diet.…”
Section: Discussionmentioning
confidence: 91%
“…Subsequent studies reported by this Japanese group indicated that the hops-derived isohumulones reduced elevated triglycerides associated with insulin resistance, and raised HDL cholesterol levels while reducing liver fat stores in diabetic animal models [19,20]. In a companion study this same group reported that the administration of isohumulones prevented high fat diet-induced obesity in the C57BL/6N mouse model [21]. Nozawa et al also reported that dietary supplementation with isohumulones was found to reduce the production of the proinflammatory prostaglandin E 2 in the rat colon suggesting a tissue-specific anti-inflammtory effect [22].…”
Section: Influence Of Hops Isohumulones (Iso-alpha Acids) On Inflammamentioning
confidence: 91%
“…In addition to these effects hops-derived compounds (including iso -alpha acids) have been found to block TNF-α-induced production of IL-6 and to inhibit the transactivation of NF-κB, activator protein-1 (AP-1), and cAMP-response element-binding protein (CREB) in fibroblasts [17]. More recently, it has been proposed that hops has positive impact on adipocyte metabolism [18] and glucose tolerance in obese and diabetic rodents; however, the exact mechanisms explaining these effects are not well characterized [19], [20]. Therefore, in the present study we investigated the impact of a well-defined hop extract (META060) on body weight gain, fat mass development, glucose homeostasis and gut barrier function markers in diet-induced obese and type 2 diabetic mice.…”
Section: Introductionmentioning
confidence: 99%